EKSPRESORIA - Arif Hutria; Esy Maestro; Yensharti Yensharti (SENDRATASIK UNP, 2013)
Abstract The idea in this artwork was started from the expression of feeling which is channeled into expression. Then, this expression was expressed into musical compositions that is interpreted in tones of melody, harmony, and rhythm that is composed into musical expression of feeling. This artwork was created by implementing some artwork methodologies; they were exploration, document analysis, experiment, and formation phase. This musical composition was also done in 3 parts of composition, namely Part A, Part B, and Part C. The Part A shows a calm expression in happiness. Then, Part B brings “conflicts or problems" atmosphere expressed in grief, worry, full of anger emotion. In Part C the music is composed as the expression of the spirit that was so tempestuous. Music can be expressed by an artist or any one through various media, such as voice in song, musical instrument in the instrumentalia, or voice and musical instruments in the vocal-instrumental. Meanwhile, the actualization or the expression of ideas in a musical artwork can be expressed in a musical composition. Kata kunci: Ekspresi, Tahap, Komposisi